Gender and communication in Euripides' plays : between song and silence - Chong-Gossard, J. H. Kim On 1969- (Mnemosyne, Supplements, 2008)
The prominent role of women in Greek drama has always fascinated readers. This book proposes that women in Euripides' plays communicate in ways constructed by the tragic genre itself as 'female.' Yet these women's words are surprisingly not uniformly dangerous or excessively emotional, as has traditionally been thought. Rather, Euripides' women resort to 'female' ways of talking in order to enable others to understand them and their unique point-of-view. Aspects of women's speech-song, silence and secret-keeping as female verbal genres, and the challenges of speaking out of place-contribute to Euripides' portrayal of women as different from men. Originating in a culture where putting women under scrutiny was part of daily life, Euripides' tragedies dramatise women's constant struggle to control language.